A new porous Zr-containing catalyst with a phenate group: an efficient catalyst for the catalytic transfer hydrogenation of ethyl levulinate to γ-valerolactone. Issue 3 (5th January 2015) - Song, Jinliang; Wu, Lingqiao; Zhou, Baowen; Zhou, Huacong; Fan, Honglei; Yang, Yingying; Meng, Qinglei; Han, Buxing
Abstract : A new porous Zr-containing catalyst (Zr-HBA) could be used as a heterogeneous catalyst for efficient catalytic transfer hydrogenation of ethyl levulinate to γ-valerolactone. Abstract : Catalytic transfer hydrogenation (CTH) of ethyl levulinate (EL) to γ-valerolactone (GVL) is a very attractive reaction in the field of biomass transformation. In this work, a new porous Zr-containing catalyst with a phenate group in its structure was prepared by the coprecipitation of 4-hydroxybenzoic acid dipotassium salt and ZrOCl2 (Zr-HBA) in water and characterized by powder X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), N2 adsorption–desorption, and Fourier transform infrared spectroscopy. The Zr-HBA was used as the catalyst for CTH of EL to GVL in the presence of isopropanol, and the effects of temperature, time, and the amount of the catalyst on the reaction were studied. It was found that Zr-HBA was very active for the reaction and a GVL yield of 94.4% could be achieved. Meanwhile, the Zr-HBA could be reused at least five times without a notable decrease in activity and selectivity. The main reason for the high catalytic activity of the Zr-HBA was that the existence of a phenate in the structure of Zr-HBA increased the basicity of the catalyst, which is favourable for the CTH of EL.